Memory load as a cognitive antidote to performance decrements in data entry. Issue 9 (20th October 2016) - Chapman, Mary J.; Healy, Alice F.; Kole, James A.
ABSTRACT: In two experiments, subjects trained in data entry, typing one 4-digit number at a time. At training, subjects either typed the numbers immediately after they appeared ( immediate ) or typed the previous number from memory while viewing the next number ( delayed ). In Experiment 2 stimulus presentation time was limited and either nothing or a space (gap) was inserted between the second and third digits. In both experiments after training, all subjects completed a test with no gap and typed numbers immediately. Training with a memory load improved speed across training blocks (Experiment 1) and eliminated the decline in accuracy across training blocks (Experiment 2), thus serving as a cognitive antidote to performance decrements. An analysis of each keystroke revealed different underlying processes and strategies for the two training conditions, including when encoding took place. Chunking (in which the first and last two digits are treated separately) was more evident in the immediate than in the delayed condition and was exaggerated with a gap, even at test when there was no gap. These results suggest that such two-digit chunking is due to stimulus encoding and motor planning processes as well as memory, and those processes transferred from training to testing.